Sleep Disturbances and Common Mental Disorders in College Students - Byrd, Kia (2014)
OBJECTIVE: To estimate the prevalence of common mental disorders (CMDs) and examine the association of sleep disorders with presence of CMDs. METHODS: A self-administered questionnaire was used to ascertain demographic information and behavioral characteristics among 2,645 undergraduate students in Ethiopia. Standard questionnaires were used to assess CMDs, evening chronotype, sleep quality and daytime sleepiness. RESULTS: A total of 716 students (26.6%) were characterized as having CMDs. Female students had higher prevalence of CMDs (30.6%) compared to male students (25.4%). After adjusting for potential confounders, daytime sleepiness (OR=2.02; 95% CI 1.64-2.49) and poor sleep quality (OR=2.36; 95% CI 1.91-2.93) were associated with increased odds of CMDs. CONCLUSION: There is a high prevalence of CMDs comorbid with sleep disorders among college students.